AB0211 Sarcopenia in patients with inflammatory arthritis. (23rd January 2014) - Fitzpatrick, D.; McPartland, A.; Mcgowan, B.; Silke, C.; Whelan, B.
Abstract : Background: Sarcopenia is the progressive generalised loss of skeletal muscle and strength related to age and disease activity and is defined by appendicular skeletal mass/height squared (ASM/h 2 ). Sarcopenia is common in inflammatory arthritis 1 and has been linked with functional disability 2 Objectives: The aim of this study was to assess the relationship between ASM/h 2 and physical activity, fatigue, pain, and disability in inflammatory arthritis patients. Methods: Patients with inflammatory arthritis attending the NWRU were invited to take part in the study which involved the use of whole body DXA, FACIT-F and IPAQ questionnaires, HAQ-DI and routine bloods. Results: There were 11 patients in the cohort with a mean age of 67.4 and mean disease duration of 17 years. A positive correlation existed between ASM/height 2 and physical activity (R=.714, p=.047). There was a negative correlation between VAS Pain and physical wellbeing (R=.-764, p=.010), functional wellbeing (R= -.828, p=.003), FACIT-fatigue (R= -.634, p=.049) and a positive correlation between VAS Pain and the HAQ-DI (R=.732, p=.025). VAS Fatigue correlated negatively with physical wellbeing (R= -.752, p=.012) and positively with HAQ-DI (R=.621, p=.044). No significant correlation was found between ASM/height 2 and HAQ-DI or fatigue. Conclusions: As expected, ASM/h 2 is correlated with physical activity but somewhat surprisingly not with fatigue or functional ability. The numbers of subjects included is very low and as such all findings will have to be confirmed as more subjects are added to the study. References: Giles J, Ling S, Ferrucci L. Abnormal body composition phenotypes in older rheumatoid arthritis patients: association with disease characteristics and pharmacotherapies. Arthritis Care & 2008. Available at: http://onlinelibrary.wiley.com/doi/10.1002/art.23719/full . Accessed June 29, 2012. Janssen I, Heymsfield S. Low relative skeletal muscle mass (sarcopenia) in older persons is associated with functional impairment and physical disability. Journal of the American . 2002:889-896. Available at: http://onlinelibrary.wiley.com/doi/10.1046/j.1532-5415.2002.50216.x/full . Accessed June 29, 2012. Disclosure of Interest: None Declared